Epithelioid sarcoma – a case report and literature review - Gliński, Bogdan; Dymek, Paweł; Ryś, Janusz; Walasek, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2008)
Epithelioid sarcoma (ES) is a very rare high-grade soft tissue sarcoma with a known propensity for locoregional recurrence and dissemination. ES compromises less than 1% of soft tissue sarcomas, with a predisposition for young male adults. ES occurs most often at distal upper limb locations. Surgery remains the basic treatment option. Precise information on survival and prognostic factors is difficult to ascertain, due to the rarity of the disease. The 5-year and 10-year survival rates have been reported to be in the range of 25% to 78% and 25% to 74% respectively. The place and role of adjuvant postoperative therapy schedules for patients with ES are unclear and need further research. A 29-year-old man with histopathologically confirmed ES of the distal upper limb was admitted to the Centre of Oncology in Cracow. Development of a mass was the main presenting symptom. The staging was established as unifocal limited disease. The patient was treated with limb sparing surgery. Because of high-grade (G3) histology, two courses of chemotherapy with Adriamycin were given, followed by postoperative irradiation, with a total dose of 68.4 Gy. Treatment was well tolerated; very good functional and cosmetic results were obtained. The patient has no evidence of disease at the last follow-up, four years after completion of treatment.